LICENSURE EXAMINATION PERFORMANCE OF TEACHER EDUCATION GRADUATES - MARAMAG, ARIEL M. (International Journal of Psychosocial Rehabilitation, 2020)
Teacher Education institutions consider performance in the Licensure Examination for Teachers (LET) as a measure of educational quality geared towards skills development expected of graduates. Hence, this paper aimed to determine the LET performance among the first time takers of Teacher Education graduates from the Bachelor of Secondary Education program during the September 2017 testing period. It made use of descriptive research design with the use of documentary analysis as its primary data gathering tool. Specifically, it described the LET performance of the first-time takers in the areas General Education, Professional Education, and Specialization. Results show that the LET performance of the BSED graduates is generally fair. Categorically, the findings show that they have satisfactory performance along General Education, fair along Professional Education, and poor along their Specialization. In the light of the findings of the study, it is concluded that although recent Licensure Examination for Teachers (LET) performance of the BSED graduates is higher than the national passing rate, there is generally a need to improve their LET performance. The poor performance in the Specialization area for the secondary education graduates calls for immediate action which can be translated into a University policy for the improvement of the graduates’ LET performance.